Exanthema in human immunodeficiency virus disease, manifestation of infection or allergic reaction? - Bertozzi, Silvano (2023)
A male patient presented with a maculopapular, non-pruritic rash, without palmoplantar involvement, after receiving treatment with trimethoprim/sulfamethoxazole for seven days due to gastrointestinal symptoms. After taking a complete medical history and using fourth-generation tests confirmed HIV infection. On the fifth day of antiretroviral treatment, he presented new erythematous lesions with thick, pruritic scaling, facial edema and eosinophilia. A skin biopsy reported lichenoid dermatitis, with spongiosis, vacuolar degeneration of the basal layer, necrotic keratinocytes and eosinophil infiltrate, characteristics that favor drug reaction. The treatment consisted of interrupting the combined therapy, using systemic corticosteroids, antihistamines and since it was not a severe condition, antiretroviral treatment restarted without complications.